Informed Consent in Clinical Studies Involving Human Participants: Ethical Insights of Medical Researchers in Germany and Poland - Timmermann, Cristian; Orzechowski, Marcin; Kosenko, Oxana; Woniak, Katarzyna; Steger, Florian (Frontiers in Medicine, 2022)
Background: The internationalization of clinical studies requires a shared understanding of the fundamental ethical values guiding clinical studies. It is important that these values are not only embraced at the legal level but also adopted by clinicians themselves during clinical studies. Objective: Our goal is to provide an insight on how clinicians in Germany and Poland perceive and identify the different ethical issues regarding informed consent in clinical studies. Methods: To gain an understanding of how clinicians view clinical studies in the countries they work in, we carried out semi-structured problem-centered interviews per telephone in Poland (n=6) and Germany (n=6). Our interviewees concentrated on three main topics: an appraisal of the normative framework, challenges in the information process and the protection of all participants in clinical studies. Results: Clinicians generally supported the normative framework, even though they considered it quite complex. In the two study countries a widely noted dilemma in the information process was whether to overburden participants with extensive information or risking leaving out important facts. Clinicians were ready to exclude larger population groups from participating in clinical studies when the information process could not be carried out with standard procedures or when their inclusion was ethically sensitive. Conclusion: Clinicians need to gain a better understanding of the consequences of excluding larger population groups form participating in clinical studies. They should seek assistance in improving the information process for the inclusion of underrepresented groups in clinical studies.